Assessment variability of annual daily maximum rainfall of Kelantan, Malaysia - Siti Maizatul Ashikin, Shah Bahrim (2015)
Kelantan is one of the areas in Peninsular Malaysia that often vulnerable with a big flood and affected all local mains road. This situation prevents the help and rescue to get the flooding area. The main objectives of this study were to assess variability of annual daily maximum rainfall, to analysis annual rainfall, annual monthly maximum rainfall and annual daily maximum rainfall and to estimate expected return periods of extreme rainfall events of Kelantan, Malaysia for the period of 1998 to 2013. This study uses rainfall data derived from Tropical Rainfall Measuring Mission (TRMM) satellite-based rainfall data. The rainfall data from TRMM satellite-based for each major city in Kelantan were retrieved using Geographical Information System (GIS) technique. This study was focus on rainfall characteristics of major cities in Kelantan (Gua Musang, Kuala Krai, Jeli, Pasir Puteh, Bachok, Kota Bharu, Tumpat, Machang, Pasir Mas and Tanah Merah). Descriptive statistical analysis was conducted on annual rainfall, annual monthly and daily maximum rainfall. Gumbel distribution function was applied to estimate return periods of extreme rainfall events. It was found that annual daily maximum rainfall for Pasir Putih, Kelantan is 616.13 mm which had a return period of 100 years was the highest maximum annual daily rainfall estimated. For future, the result from this study could be used as a guideline in planning and designing any infrastructure in Kelantan, Malaysia